2015
DOI: 10.3390/w7020818
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Escherichia coli in Rivers of Northern Coastal Ecuador

Abstract: The use of contaminated surface water continues to be a pressing issue in areas of the world where people lack improved drinking water sources. In northern coastal Ecuador, many communities rely on untreated surface water as their primary source of drinking water. We undertook a study to explore how microscale river hydrodynamics affect microbial water quality at community water collection locations at three rivers with varying stream velocity and turbidity profiles. To examine how the distance from river shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
3
17
0
2
Order By: Relevance
“…For example, turbidity was ranked as an important factor in 7 of the 15 random forest analyses performed here, and was associated detecting pathogens in samples collected from both AZ and NY waterways. Multiple studies (Christensen et al, 2000; Francy et al, 2013; Havelaar et al, 2017; Horman et al, 2004; Nagels et al, 2002; Rao et al, 2015; Topalcengiz et al, 2017), including the study reported here and the Ecuadorian study discussed above (Rao et al, 2015), found a positive association between E. coli levels and temperature, or between E. coli levels and turbidity. Francy et al (Francy et al, 2013) surveyed recreational water quality at 22 Ohio beaches along inland lakes and found that turbidity was one of the best predictors of E. coli levels.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…For example, turbidity was ranked as an important factor in 7 of the 15 random forest analyses performed here, and was associated detecting pathogens in samples collected from both AZ and NY waterways. Multiple studies (Christensen et al, 2000; Francy et al, 2013; Havelaar et al, 2017; Horman et al, 2004; Nagels et al, 2002; Rao et al, 2015; Topalcengiz et al, 2017), including the study reported here and the Ecuadorian study discussed above (Rao et al, 2015), found a positive association between E. coli levels and temperature, or between E. coli levels and turbidity. Francy et al (Francy et al, 2013) surveyed recreational water quality at 22 Ohio beaches along inland lakes and found that turbidity was one of the best predictors of E. coli levels.…”
Section: Discussionsupporting
confidence: 46%
“…This suggests that E. coli levels were more strongly associated with physiochemical water quality than weather for the waterways sampled during our study. Previous studies have repeatedly identified associations between physiochemical water quality and E. coli levels (Ansa et al, 2011; Christensen et al, 2000; Horman et al, 2004; Rao et al, 2015; Roslev et al, 2004; Stocker et al, 2016). Similar to our study, a study that examined the microbial and physiochemical quality of three Ecuadorian rivers found a negative association between dissolved oxygen and E. coli levels (Rao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread of E. coli population was poorly recorded and studied in Pasuruan. Rao et al (2015) found the way to inform community members about the safest locations to get drinking water and watershed scale transport of microbial contaminants/ between villages [8]. Recently, people take the drinking water from drinking water station.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…En el Ecuador existen comunidades que dependen del agua superficial no tratada como su fuente primaria de agua potable (Rao et al, 2015). Lamentablemente, estas fuentes superficiales son el sumidero de aguas servidas que contienen residuos humanos con una gran carga bacteriana, en especial de coliformes fecales.…”
Section: Introductionunclassified